Kinerja Tim Teknis Pelayanan Izin Mendirikan Bangunan (IMB) pada Dinas Tata Kota Manado - Sukarnaen, Purwati; Mamentu, Michael; Tasik, Femmy (JURNAL ILMIAH SOCIETY, 2016)
The study aims to find the reasons for poor performance in implementing the tasks of the Technical Team IMB service. As for performance measurement indicators used in this study is the productivity, quality of service, responsiveness, responsibility and accountability. This study used a qualitative design. The processed data in this study are primary data and secondary data. Assessed in terms of the productivity of the work done by the technical team at the Department of City Planning has not been optimal Manado good jobs received, performed and produced. Lack of manpower Technical Team IMB service in Manado City Planning Office. Facilities and infrastructure inadequate survey. Quality of service is still considered slow and tortuous. Technical Team Performance less than the maximum because they have to work under the coordination of the two lines. In terms of the responsiveness of the technical team is less sensitive in recognizing the needs of the community so that the process is less than the maximum file handling. Responsibility in terms of the lack of coordination and communication between the technical team with BP2T result is not optimal care. In terms of performance accountability Technical Team pertaining to the service is quite accountable. Technical Team IMB has published Recommendation seeks to maintain the norms that exist in society by taking into account environmental impact. With the lack of working facilities No Technical Team are still working to achieve revenue targets (regional revenue) that have been defined. Keywords: Performance Technical Team, Public services, Optimal